2018
DOI: 10.1103/physrevlett.120.156403
|View full text |Cite
|
Sign up to set email alerts
|

Band Structure of the IV-VI Black Phosphorus Analog and Thermoelectric SnSe

Abstract: The success of black phosphorus in fast electronic and photonic devices is hindered by its rapid degradation in the presence of oxygen. Orthorhombic tin selenide is a representative of group IV-VI binary compounds that are robust and isoelectronic and share the same structure with black phosphorus. We measure the band structure of SnSe and find highly anisotropic valence bands that form several valleys having fast dispersion within the layers and negligible dispersion across. This is exactly the band structure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
55
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 48 publications
(83 reference statements)
8
55
1
Order By: Relevance
“…Thus, the most critical value for determining the hyperbolic regime is not the effective mass ratio, but the anisotropy of the intraband and interband couplings along the two principle axes. In layered anisotropic semiconductor materials, such as BP, BP‐analog materials (e.g., SnSe, SnS, GeSe, and GeS), the 1T phase of TMDCs (e.g., ReSe 2 ), and the trichalcogenides (e.g., TiS 3 ), strong anisotropic in‐plane electronic properties have been demonstrated via anisotropic optical absorptions, polarization‐dependent PL, and anisotropic conductivities, while the low carrier densities (low intensity of intraband transitions) and relatively large bandgap (from the mid‐infrared to the visible spectrum) are against forming strong coupling between the intraband and interband excitations unless the plasmon frequencies are tuned to the vicinity of interband excitations. In such cases, the wave vector for plasmons would be extremely large, which is impractical in experiments.…”
Section: Plasmons In Anisotropic 2d Materialsmentioning
confidence: 99%
“…Thus, the most critical value for determining the hyperbolic regime is not the effective mass ratio, but the anisotropy of the intraband and interband couplings along the two principle axes. In layered anisotropic semiconductor materials, such as BP, BP‐analog materials (e.g., SnSe, SnS, GeSe, and GeS), the 1T phase of TMDCs (e.g., ReSe 2 ), and the trichalcogenides (e.g., TiS 3 ), strong anisotropic in‐plane electronic properties have been demonstrated via anisotropic optical absorptions, polarization‐dependent PL, and anisotropic conductivities, while the low carrier densities (low intensity of intraband transitions) and relatively large bandgap (from the mid‐infrared to the visible spectrum) are against forming strong coupling between the intraband and interband excitations unless the plasmon frequencies are tuned to the vicinity of interband excitations. In such cases, the wave vector for plasmons would be extremely large, which is impractical in experiments.…”
Section: Plasmons In Anisotropic 2d Materialsmentioning
confidence: 99%
“…Since the overlapping of several bands in SnSe and the large momentum intervals of the spectra for some measured directions have prevented us from estimating the lifetime for each band from the momentum distribution curves, we instead estimate the lifetime from the energy distribution curves After completion of this work, we became aware of an ARPES study on SnSe, 27) which reported the in-plane effective masses for the two valence-band extrema and presented a similar discussion on the origin of the high thermoelectric performance. In an ARPES experiment, one can determine the momentum normal to the cleavage plane (a plane) by using a free-electron final-state model.…”
Section: (E)-2(g) the Deduced Values Are Mmentioning
confidence: 99%
“…As a candidate for this, we focus on SnSe, which has very recently attracted significant attention due to the high thermoelectric figure of merit at around 900 K [12]. In addition to the ultra-low thermal conductivity, the multi-valley valence bands have been suggested as an origin of the excellent performance [13][14][15][16][17][18][19]. Therefore, we here aimed to drive the Lifshitz transition by employing hydrostatic pressure to continuously tune the relative band-filling of the multivalley states for SnSe.…”
mentioning
confidence: 99%
“…The present result demonstrates the multi-valley state is of great importance for achieving high thermoelectric performance, providing a guide for band engineering for the SnSe-based thermoelectrics. Furthermore, since atomically thin SnSe films have recently attracted much attention as a new 2D material [18,42], the controllability of valley structure presented here will help for exploring their novel functions in the emerging valleytronics. [29] P. E. Blöchl, Phys.…”
mentioning
confidence: 99%